Development of Seebeck-Coefficient Measurement Systems Using Kelvin-Probe Force Microscopy - Miwa, Kazutoshi; Salleh, Faiz; Ikeda, Hiroya (Makara Journal of Technology, 2013)
Thermoelectric device is investigated by a number of researchers in order to enhance the thermoelectric efficiency. It is known that the efficiency can be improved by quantum effect. However, it is difficult to measure the thermoelectric characteristics of nanometer-scale structures. Thus a new measurement method is expected to be developed. We propose to apply Kelvin-probe force microscopy (KFM) to characterization of thermoelectric materials. KFM can locally observe surface potential of Fermi energy of a sample without touching the sample surface. In the present paper, we estimate the Seebeck coefficient of thin Si-on-insulator layers using KFM.